Conceptualizing Context and Intervention as a System in Implementation Science: Learning From Complexity Theory; Comment on "Stakeholder Perspectives of Attributes and Features of Context Relevant to Knowledge Translation in Health Settings: A Multi-country Analysis" - Lisa M. Pfadenhauer (Kerman University of Medical Sciences, 2022)
In implementation science, implementation has been widely theorized and assessed. Context, on the other hand, usually played a minor role in the field and was usually conceptualized in a rather positivist way. Despite some promising efforts, there is a strong need to continue building theory on context and operationalizing the concept in implementation practice. I argue for the benefit of integrating complexity theory into our understanding of context in order to further our thinking about context and intervention as a system. This should be reflected by the way in which we build theory as well as apply this theory by employing methods that adequately account for complexity in systems.